Isotope composition of daily precipitation from 2019 to 2020 in Sanming, southeastern China - Cai, Jianrong; Yang, Yunyue; Yang, Zhijie; Qiu, Wanyin; Jiang, Xiuyang (Frontiers in Environmental Science, 2022)
Many studies in southeastern China (SEC) have used stable isotope (δD and δ18O) records from natural archives (e.g. stalagmites, tree-ring cellulose, sediments) to reconstruct past East Asian Summer Monsoon (EASM) climate. However, the interpretation of the meanings of isotope variation in these records has not been fully resolved, and the key to solve this problem is to clarify the referential meaning of modern precipitation isotopes. This study is intended to clarify the characteristics of isotope variations and their controlling factors during different seasonal periods (e.g., non-summer monsoon (NSM) and summer monsoon (SM)) in SEC. Our results show that the precipitation δ18O (δ18Op) and d-excess values in the SM season (-12.94‰–0.15‰, -4.05‰–21.01‰) were more light than those in the NSM season (-6.91‰–4.37‰, 0.85‰–30.38‰). Combining the findings of backward trajectory and averaged outgoing longwave radiation analyses, the seasonal variation of precipitation isotopes is believed to be determined by a shift in water vapor sources and the intensity of upstream atmospheric convection during water vapor transportation. The consistent variation between the isotope values and convective intensity over the South China Sea in the dragon boat rainy period highlights that δ18Op has the potential to respond rapidly to the upstream convective intensity and can serve as a substitute method for investigating the complicated East Asian summer monsoon system. Therefore, the results of this study imply that the stable isotopes in precipitation and related paleoclimate proxies may not reflect the signal of temperature or precipitation alone but rather reflect changes in moisture sources and upstream convective intensity.